**Problem : **
Solve the following system using Cramer's Rule:

(x+y+z= 7

2x- 2y+ 3z= 14

-x-y+z= 1

**Problem : **
Solve the following system using Cramer's Rule:

2(x+ 3y+z= - 3

3x+ 2z= 7

x+ 2y+z= 0

**Problem : **
Solve the following system using Cramer's Rule:

(x+ 2y+ 2z= 0

2x-y- 6z= - 5

2y+ 5z= 6

**Problem : **
Solve the following system using Cramer's Rule:

2(x+ 2y+z= 2

x+y+z= 3

3x+ 5y+ 2z= 2

**Problem : **
Solve the following system using Cramer's Rule:

(x+y- 3z= - 4

4x+ 2y- 6z= - 2

5x+ 5y+ 4z= 4